2019
DOI: 10.1039/c9tc02924a
|View full text |Cite
|
Sign up to set email alerts
|

In situ monitoring of plasmon-driven photocatalytic reactions at gas–liquid–solid three-phase interfaces by surface-enhanced Raman spectroscopy

Abstract: Plasmon-driven photocatalytic reaction is monitored at the gas-liquid-solid interface by using superhydrophobic surface enhanced Raman spectroscopy (SERS) substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…64,233 In this case, the surface ability to sustain a gas layer in close proximity to reaction sites is crucial to sustaining an ongoing reaction. 64,233,236 Complementary to this, underwater gas transportation becomes essential in many processes, including underwater micro-reactions, water treatment, and selective aeration. [237][238][239][240][241] Whether gases are meant to be delivered to the reaction place or removed away from it, controlling the bubbles pathway is important for process completion.…”
Section: Underwater Gas/involving Reactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…64,233 In this case, the surface ability to sustain a gas layer in close proximity to reaction sites is crucial to sustaining an ongoing reaction. 64,233,236 Complementary to this, underwater gas transportation becomes essential in many processes, including underwater micro-reactions, water treatment, and selective aeration. [237][238][239][240][241] Whether gases are meant to be delivered to the reaction place or removed away from it, controlling the bubbles pathway is important for process completion.…”
Section: Underwater Gas/involving Reactionsmentioning
confidence: 99%
“…244 Gao et al have utilized surface-enhanced Raman spectroscopy (SERS) to investigate the effect of surface wetting behaviour on the plasmon-driven catalytic-coupling reaction of p-aminothiophenol (PATP) into p,p 0 -dimercaptoazobenzene (DMAB), which require the presence of O 2 as an oxidizing agent for PATP molecules. 236 A hierarchical surface made from silver micro-balls decorated with silver nano-dendrites was employed as a SERS active reaction surface, and surface-modification was carried out to make samples with different wetting behaviours; hydrophilic, hydrophobic and superhydrophobic. 236 It was revealed that for superhydrophobic surfaces, a higher Raman intensity was detected for PATP binding to the catalyst surface, indicating an increase in the reaction dynamics.…”
Section: Underwater Gas/involving Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the degradation of pollutants, there are many other triphase interfacial photocatalytic studies involving oxygen, such as the in situ monitor of photocatalytic reaction at triphase interfaces, [ 17 ] the mechanistic research on the photooxidation of the first triphasic superhydrophobic sensitizer, [ 18 ] the inactivation of Klebsiella pneumoniae in the triphase system, [ 19 ] and the oxygen reduction at the triphase interface for efficient hydrogen peroxide generation. [ 20 ]…”
Section: Gas‐consuming Reactionsmentioning
confidence: 99%
“…Triphase interface photocatalytic reaction systems can also be used to boost plasmon-driven photocatalytic reactions, semiconductor-mediated photodegradation and other photo-energy conversion reactions as long as gaseous reactants are involved. [13][14][15][16] 2.2 Bio-(photo)electrochemical reactions…”
Section: Photocatalytic Reactionsmentioning
confidence: 99%